ANALISIS PENGARUH MANAJEMEN MATERIAL TERHADAP KUALITAS KINERJAPELAKSANAAN PROYEK KONSTRUKSI GEDUNG DI KOTA DENPASAR - Putu Eny Suhardiyani; I Putu Widyarsana; Ni Kadek Sri Ebtha Yuni (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
A construction project is an activity to achieve results in the form of infrastructure. Therefore, good resource management is needed so that the project is cost effective, on time and meets the specified quality. With good control on material management, contractors will benefit from the effective use of materials. This study aims to determine the effect of material management on the performance quality of building construction projects in Denpasar City. This research method was carried out quantitatively and qualitatively. Data analysis using Multiple Linear Regression Analysis with the help of SPSS 19.0 application. Based on the results of the analysis in this study partially, material procurement planning is in accordance with specifications, material purchases are in accordance with the planning, material delivery according to specifications and installation schedules, material storage and security, material use in accordance with material characteristics, and material control by the logistics department has an effect on performance quality of construction project implementation. While testing the coefficient of determination shows that all independent variables in this study have significant effect on the quality of performance construction project implementation by 83.2% (R = 0.832), and the remaining 16.8% is influenced by other factors not included in this study.